Johann Philipp Gabier and the consequences: in search of a new paradigm for Old Testament Theology - Wittenberg, Gunther (Old Testament essays, 1995)
Old Testament Theology as a discipline is generally considered to have been initiated by Johann Philipp Gabier. Issues present are the quest for certainty, the emphasis on methodology, the systematic presentation of religious ideas as the task of Old Testament Theology, the rejection of the individual and specific in favour of the generalised and timeless, the use of historical criticism as a preliminary tool while at the same time denying the validity of history for theology. We need to develop a new approach to Old Testament Theology belonging to a different 'knowledge system in which not religious ideas but oentext and commitment would be fundamental and in which the insights of social scientists (Geertz and Weber) have to make important contributions.